2023
DOI: 10.3390/ijms241310943
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammation after Aneurysmal Subarachnoid Hemorrhage

Abstract: Aneurysmal subarachnoid hemorrhage (aSAH) is one of the most severe neurological disorders, with a high mortality rate and severe disabling functional sequelae. Systemic inflammation following hemorrhagic stroke may play an important role in mediating intracranial and extracranial tissue damage. Previous studies showed that various systemic inflammatory biomarkers might be useful in predicting clinical outcomes. Anti-inflammatory treatment might be a promising therapeutic approach for improving the prognosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 291 publications
(346 reference statements)
1
8
0
Order By: Relevance
“…Second, the prognosis and DCI of aSAH are closely related to the overall condition of the body 35 . aSAH not only damages brain tissue but also triggers systemic oxidative stress and inflammatory reactions 36 . AIM2 can promote the production of inflammatory factors interleukin-1β and interleukin-18 and cause intracellular damage when specifically activated 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Second, the prognosis and DCI of aSAH are closely related to the overall condition of the body 35 . aSAH not only damages brain tissue but also triggers systemic oxidative stress and inflammatory reactions 36 . AIM2 can promote the production of inflammatory factors interleukin-1β and interleukin-18 and cause intracellular damage when specifically activated 37 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the injury occurring in the ictal phase, secondary damage triggered by cerebral vasospasm and delayed cerebral ischemia has a determining effect on the outcome. Based on experimental and clinical research, there is growing evidence that neuroinflammation plays a pivotal role in both early and delayed injury [4,[19][20][21]. Studies have shown that, in up to 60% of patients with hemorrhagic stroke, a systemic inflammatory response syndrome may develop [8].…”
Section: Discussionmentioning
confidence: 99%
“…Hemorrhagic stroke frequently results from subarachnoid hemorrhage ( 99 ). An essential factor in developing subarachnoid hemorrhage is inflammation ( 105 ). In one study by Lai et al ( 83 ), modified exosomes were utilized to deliver miR-193b-3p in mice with subarachnoid hemorrhage.…”
Section: Application Of Modified Exosomal Therapeutics Delivery In Brainmentioning
confidence: 99%